Form and forces - Allen, Edward (John Wiley & Sons, Inc, 2010)
Includes bibliographical references and index.; Designing a series of suspension footbridges -- Designing a suspended roof -- Designing a concrete cylindrical shell roof -- Master lesson: designing a trussed roof -- Designing a building on a vertical site -- Designing with multipanel trusses -- Designing a fanlike roof -- Designing unreinforced masonry -- Master lesson: designing a concrete shell roof for a grandstand -- Desiging efficient trusses -- Designing restraints for funicular structures -- Designing shell and membrane structures -- Structural materials -- Master lesson: designing with the flow of forces -- Designing a bay of framing -- Bending actions on beams -- How beams resist bending -- Bending resistance in beams of any shape -- Designing columns, frames, and load-bearing walls -- Designing a sitecast concrete building -- Master lesson: designing in precast concrete -- Designing an entrance canopy -- Afterword: engineers and architects.